DIGITAL GAME DEVELOPMENT AS A COMPUTER SCIENCE LEARNING TOOL FOR VOCATIONAL HIGH SCHOOL STUDENTS - Roswina Dianawati; Lyau Nyan Myau; Widiyanti Widiyanti (Universitas Negeri Malang, 2022)
Indonesia has a shortage of professionals in Information and Communications Technology (ICT). Therefore, to increase the pool of electrical experts who are also qualified in the field of computer science, it is necessary to boost interest in computer science at an early year of upper secondary level. The Game Based Learning (GBL) approach increased investment in computer science for vocational high school learners. The two-dimensional (2D) game named Jack into Woods (JIW) was developed to teach fundamental concepts of C++ programming and influence the view in the computer science fields of electrical engineering of vocational high school students. The research involved the instructional design procedure, particularly the ADDIE model, to build and observe the computer game prototype and whether the product contextually fulfills the feasible and practical standard. The quantitative research method study was used to analyze the measurement. A total of 4 experts, 32 students from the pilot study group and 64 students from the control and experiment groups, participated in the research. The data was collected from research participants through pre-test–post-test, and pre-survey–post-survey responses. The quantitative data was collected, and feasibility was analyzed using descriptive statistics. Although participants scored significantly different between experiment and control groups’ post-survey responses, the focus and control groups’ post-test performances were not significantly different.